Unexpected high binding energy of CO2 on CH3NH3PbI3 lead-halide organic–inorganic perovskites via bicarbonate formation. Issue 71 (17th August 2018) - Nayakasinghe, M. T.; Han, Yulun; Sivapragasam, N.; Kilin, Dmitri S.; Burghaus, U.
Abstract : The adsorption kinetics of CO2 was experimentally characterized in ultra-high vacuum (UHV). In addition, density functional theory (DFT) calculations were included. Abstract : The adsorption kinetics of CO2 was experimentally characterized in ultra-high vacuum (UHV). Unexpectedly, high desorption temperatures (640 K, 170 kJ mol −1 ) were seen. Density functional theory (DFT) calculations suggest the stabilization mechanism: bicarbonate formation in the defected perovskite film due to CO2 and H2 O coadsorption.